Regulatory changes in TaSNAC8‐6A are associated with drought tolerance in wheat seedlings. Issue 4 (19th November 2019) - Mao, Hude; Li, Shumin; Wang, Zhongxue; Cheng, Xinxiu; Li, Fangfang; Mei, Fangming; Chen, Nan; Kang, Zhensheng
Summary: Wheat is a staple crop produced in arid and semi‐arid areas worldwide, and its production is frequently compromised by water scarcity. Thus, increased drought tolerance is a priority objective for wheat breeding programmes, and among their targets, the NAC transcription factors have been demonstrated to contribute to plant drought response. However, natural sequence variations in these genes have been largely unexplored for their potential roles in drought tolerance. Here, we conducted a candidate gene association analysis of the stress‐responsive NAC gene subfamily in a wheat panel consisting of 700 varieties collected worldwide. We identified a drought responsive gene, TaSNAC8‐6A, that is tightly associated with drought tolerance in wheat seedlings. Further analysis found that a favourable allele TaSNAC8‐6A In‐313, carrying an insertion in the ABRE promoter motif, is targeted by TaABFs and confers enhanced drought‐inducible expression of TaSNAC8‐6A in drought‐tolerant genotypes. Transgenic wheat and Arabidopsis TaSNAC8‐6A overexpression lines exhibited enhanced drought tolerance through induction of auxin‐ and drought‐response pathways, confirmed by transcriptomic analysis, that stimulated lateral root development, subsequently improving water‐use efficiency. Taken together, our findings reveal that natural variation in TaSNAC8‐6A and specifically the TaSNAC8‐6A In‐313 allele strongly contribute to wheat drought tolerance and thus represent a valuable genetic resource for improvement of drought‐tolerant germplasm for wheat production.